The Influence of Fatherlessness on Mental Health in Lubuk Buaya Village as an Effort to Strengthen Mental Health Literacy - Silvia Yunesta; Wira Solina; Rahmawati Wae (Global Action and Education for Society, 2026)
This research is motivated by the presence of teenagers who experience excessive anxiety when in a new environment, teenagers who are unable to adapt well, and teenagers who cannot manage stress in a healthy way. This research aims to determine: 1) fatherlessness among adolescents in Lubuk Buaya village, 2) the mental health of adolescents in Lubuk Buaya village, 3) the influence of fatherlessness on mental health in Lubuk Buaya village. This study uses a correlational quantitative research method. The population of this study consists of 40 people. The sampling technique used is total sampling. The instrument used in this study is a questionnaire. The data analysis in this study is percentage and simple linear regression. The results of this study show: 1) Fatherlessness among adolescents in Lubuk Buaya village is in the fairly high category. 2) The mental health of adolescents in Lubuk Buaya village is in the fairly good category. 3) There is an influence of fatherlessness on the mental health of adolescents in Lubuk Buaya village with a very low coefficient value of 0.010. Based on the results of this study, it is recommended for teenagers to improve paternal interaction, specifically the involvement of fathers in parenting by spending time directly with their children. Then, in terms of mental health, teenagers should be able to avoid and anticipate mental disorders and mental illnesses. Additionally, it is also recommended for the sub-district to inform the surrounding community about programs to support families and children experiencing fatherlessness, as well as to raise public awareness about the importance of the father's role in child-rearing.